Hotel Selection Criteria of Solo Traveling Females - Halimin Herjanto; Alexandra Chilicki; Chidchanok Anantamongkolkul; Erin McGuinness (Centre For Tourism Planning and Development, 2020)
Consumers use online e-reviews as a popular tool for information and obtaining guidance. E-reviews have therefore become an important barometer in conducting product evaluations, and more importantly, to make purchasing decisions. This includes decisions about hotel selection. For hospitality industry marketers, the information in e-reviews is particularly important in translating and understanding consumer-specific needs. The current study brings valuable awareness to the limited academic research into hotel selection criteria among solo-traveling females. TripAdvisor's top 25 list of cost-efficient hotels worldwide received 345 total consumer reviews. Noteworthy findings of the current study show unique selection criteria considered important to the solo traveling female including a hotel-provided cell phone programmed with emergency local contact information, and a nearby or on-premise automated teller machine. Study results also indicate that stewardship service, such as intimate and personalized hotel staff who